2022
DOI: 10.1037/pha0000449
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cigarette smoking: Comparisons of global self-report, returned cigarette filters, and ecological momentary assessment.

Abstract: Prior work suggests that prospective measurement of cigarette use may be more reliable and valid than retrospective self-reports. Despite several studies comparing retrospective and prospective methods, there are a myriad of prospective methods that have not been directly compared, including spent cigarette filters that are returned to the laboratory by participants and diary logs of cigarette use on an electronic device via ecological momentary assessment. The current secondary data analysis compared the reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Including this small window around diary entries limited recall errors while improving participant compliance. Other research has demonstrated high degree of congruity between eDiary logs and actual combustible cigarette use [ 37 ]. Since all TNP uses were captured, the risk of differential recall for cigarettes versus pouches would be minimal and unlikely to be biasing.…”
Section: Discussionmentioning
confidence: 99%
“…Including this small window around diary entries limited recall errors while improving participant compliance. Other research has demonstrated high degree of congruity between eDiary logs and actual combustible cigarette use [ 37 ]. Since all TNP uses were captured, the risk of differential recall for cigarettes versus pouches would be minimal and unlikely to be biasing.…”
Section: Discussionmentioning
confidence: 99%